Resilience of terrestrial and aquatic fauna to historical and future wildfire regimes in western North America - Jager, Henriette I.; Long, Jonathan W.; Malison, Rachel L.; Murphy, Brendan P.; Rust, Ashley; Silva, Luiz G. M.; Sollmann, Rahel; Steel, Zachary L.; Bowen, Mark D.; Dunham, Jason B.; Ebersole, Joseph L.; Flitcroft, Rebecca L. (Ecology and evolution, 2021)
Wildfires in many western North American forests are becoming more frequent, larger, and severe, with changed seasonal patterns. In response, coniferous forest ecosystems will transition toward dominance by fire‐adapted hardwoods, shrubs, meadows, and grasslands, which may benefit some faunal communities, but not others. We describe factors that limit and promote faunal resilience to shifting wildfire regimes for terrestrial and aquatic ecosystems. We highlight the potential value of interspersed nonforest patches to terrestrial wildlife. Similarly, we review watershed thresholds and factors that control the resilience of aquatic ecosystems to wildfire, mediated by thermal changes and chemical, debris, and sediment loadings. We present a 2‐dimensional life history framework to describe temporal and spatial life history traits that species use to resist wildfire effects or to recover after wildfire disturbance at a metapopulation scale. The role of fire refuge is explored for metapopulations of species. In aquatic systems, recovery of assemblages postfire may be faster for smaller fires where unburned tributary basins or instream structures provide refuge from debris and sediment flows. We envision that more‐frequent, lower‐severity fires will favor opportunistic species and that less‐frequent high‐severity fires will favor better competitors. Along the spatial dimension, we hypothesize that fire regimes that are predictable and generate burned patches in close proximity to refuge will favor species that move to refuges and later recolonize, whereas fire regimes that tend to generate less‐severely burned patches may favor species that shelter in place. Looking beyond the trees to forest fauna, we consider mitigation options to enhance resilience and buy time for species facing a no‐analog future. Wildfires in many western North American forests are becoming more frequent, larger, and more severe due to changes in climate and past fire suppression. We propose a new life history framework for wildlife response to frequency, intensity, and patch size of wildfire disturbances. Finally, we consider forest management strategies that might enhance the resilience of wildlife under transient future conditions.